Comparative study on combustion and emissions between methanol port-injection engine and methanol direct-injection engine with H2-enriched port-injection under lean-burn conditions. (15th November 2019) - Gong, Changming; Li, Zhaohui; Yi, Lin; Liu, Fenghua
Highlights: Lean-burn strategy of H2 /methanol dual-fuel dual-injection engines is proposed. Lean-burn characteristics of homogeneous and stratified combustion modes are compared. HPI + MDI engines for 6% H2 addition can effectively extend lean-burn limit to excess air ratio 2.2. The BSHC and BSCO emissions of HPI + MPI engines are lower than these of HPI + MDI engines. The BSNOX and soot emissions of HPI + MPI engines are higher than that of HPI + MDI engines. Abstract: Lean-burn is an effective way to improve thermal efficiency and reduce emissions of spark-ignition (SI) engines. A hydrogen (H2 ) enrichment combustion strategy can extend the lean-burn limits of SI engines. Two engines equipped with hydrogen and methanol dual-port injection (HPI + MPI) and hydrogen port injection plus methanol direct injection (HPI + MDI) were used to evaluate the lean-burn capability of SI engines. The lean-burn characteristics of homogeneous and stratified combustion modes were compared. The results showed that H2 addition was more conducive to extending the lean-burn limit of the direct-injection methanol engine and achieving high indicated mean effective pressure (IMEP) than the port-injection methanol engine. HPI + MDI engines with 6% H2 addition effectively extended the lean-burn limit to an excess air ratio of 2.2. H2 addition compensated for the power drop caused by the decrease in volumetric efficiency and speed up combustion under lean-burn conditions. H2 addition could also realize stable combustion under super lean-burn conditions for HPI + MDI engines. The BSHC and BSCO emissions of HPI + MPI engines were lower than those of HPI + MDI engines, but the BSNOX and soot emissions were higher. H2 addition decreases BSCO2 emissions at the same excess air ratio for both the HPI + MPI and HPI + MDI engines.